Artificial Intelligence in Hospital Human Resource Management: A Systematic Review and Bibliometric Analysis - Efi Rusdiana; Kosasih Kosasih; Marisa Yesika; Fana Afizza Lustina; Ardio Rizky Tansil, Tan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines research trends on the application of Artificial Intelligence (AI) in hospital human resource management (HRM) and explores its implications for employee performance and career development. Research Method: A Systematic Literature Review (SLR) and bibliometric analysis were conducted on 30 articles published between 2020 and 2025. Relevant studies were identified through a structured keyword search and screened using the PRISMA protocol. VOSviewer was employed to map research trends, thematic clusters, and keyword relationships. Results and Discussion: Our major research clusters were identified as: AI and employee performance; AI in recruitment and talent management; career development and employee engagement; and digital transformation with data analytics. Publications increased substantially after 2023, reflecting growing interest in AI-driven HRM. The literature indicates a shift from operational efficiency and automation toward strategic workforce management, data-driven decision-making, talent optimization, and sustainable career development. AI is increasingly recognized as a tool for enhancing organizational adaptability and human capital effectiveness in hospitals. Implications: Healthcare organizations should integrate AI with workforce capabilities and organizational readiness to improve employee performance and support sustainable career development. Originality: This study provides a comprehensive synthesis of AI research in hospital HRM by combining PRISMA-based review procedures with bibliometric analysis.